(untitled) (London, 1995)
This book consists of the following many parts such as effects-toxicity testing, environmental fate, and assessment.
Độc chất học thủy vực
Keywords: Water quality bioassay,Toxicity testing,Water pollution,Aquatic organissms; Toxicity,Effect of water pollution on